Islam dan Lingkungan Sosial - Suarga, Suarga (Inspiratif Pendidikan, 2017)
Islam as a religion which has social paradigm is a concept of community of Islamic treatise Truth as a mercy for human beings – it lies in the perfection of Islam itself. Islam is in the unity of doctrine, between one teaching and other teachings have intertwined ascription and relationships. So, Islam can be seen simultaneously in three aspects, namely faith, Shari’ah and the nizam. In one insight, Islam is a aqidah or faith. Starting instead of Islam itself as a totality is a belief that the values taught are absolutely truth because it comes from the Supreme Absolute from all that He commanded and allowed is a haq.